Quality assessment of briquettes derived from carbonized cassava peel and sawdust as sustainable domestic sources of energy in Oyo State, Nigeria - Ajagbe, C. A.; Zainuddin, M. F.; Manaf, L. A.; Rahim, N. N. R. N. A.; Anguruwa, G. T. (Taylor and Francis, 2024)
About 80% of Nigeria’s rural and semi-urban population uses fuelwood, which accounts for 37% of the country’s energy demand. This results in the annual loss of 350,000 to 400,000 hectares of forest, increased carbon emissions, and loss of biodiversity, affecting ecosystems and quality of life. Therefore, this study was conducted to evaluate the physicochemical and combustion properties of carbonized cassava peel (CP) and sawdust (SD) hybrid briquettes as an alternative to fuelwood. Factors considered were CP/SD ratios (100:0, 75:25, 50:50, 25:75, 0:100), binder concentrations (5 and 10 g), and residence times (10, 20, 30 min). The briquettes were produced by applying a low compaction pressure of 2.4 MPa. The briquettes exhibited densities of 320.00-627.79 kg/m³, moisture content of 4.37-8.22%, water resistances of 87.26-99.85%, ash content of 5.73-41.03%, calorific values of 20.01-32.30 KJ/kg, and carbon content of 55.25-57.07%, respectively. ANOVA and Duncan’s multiple range tests revealed that CP/SD ratio is the most significant factor influencing the physicochemical and combustion properties of the briquettes. This study successfully showcased carbonized CP/SD briquettes as an alternative cooking fuel in Oyo State, leveraging the abundance of CP and SD and the feasibility of low-pressure compaction without costly equipment. © 2024 Informa UK Limited, trading as Taylor & Francis Group.